Fabrication of a mesoporous Co(OH)2/ITO nanowire composite electrode and its application in supercapacitors - Dam, Duc Tai (2013)
A novel mesoporous α-Co(OH)2/ITO NWs heterostructure has been successfully synthesized via a new method of combining chemical vapor deposition (CVD) on a titanium substrate and electrodeposition through a hexagonal lyotropic liquid crystalline (LLC) phase for electrochemical energy storage application. Electrochemical measurements demonstrate the improved ionic conductivity of an electrode and enhanced supercapacitive behavior, as compared to a mesoporous cobalt hydroxide film on a titanium current collector without indium tin oxide (ITO) NWs as “electron highways”. Galvanostatic charge–discharge measurements in 1 M KOH solution prove that the electrode of the as-prepared heterostructure possesses excellent electrochemical capacitance, in the potential range from −0.1 V to 0.5 V with a maximum specific capacitance of 1128 F g−1 at a discharge current density of 1 A g−1. The unique mesoporous α-Co(OH)2/ITO NWs heterostructure provides a high capacitance retention ratio at high discharge current densities and long-term electrochemical stability in an alkaline solution.